Membrane Filtration Application in Pre-Treatment of Crude Palm Oil - Ong, Keat Khim (1999)
The pre-treatment of crude palm oil results in loss of oil and a contaminated effluent. The objective of this research is to study the effectiveness of membrane filtration in the pre-treatment of crude palm oil for removal of phospholipids from c rude palm oil. Initial investigation with a 25,000 molecular weight cut-off, polysulfone membrane did not yield any s ignificant results. Hence, it was decided to use a PCI module, which was equipped with polyethersulfone membranes having a molecular weight cut-o ff of 9,000 (type ES209). The membrane process was carried out at 26 bar pressure and a temperature of 63±2°C. The sample, permeate and retentate were analysed for various quality parameters including phosphorus content, carotene content, free fatty acid, colour and volatile matter. The membrane e ffectively removed phospholipids resulting in a permeate with a phosphorus content of less than 0.3 ppm. The percentage removal of phosphorus was 96.4% and can be cons idered significant. Lovibond colour was reduced from 27R 50Y to 20R 30Y whereas the percentage removal of carotene was 17.5%. The removal of colour was considered good but removal of carotene was considered insignificant by the membrane. Free fatty acids and volatile matter were not removed. Typical of membrane operations, the permeate flux decreased with time and must be improved in order to be adopted on an industrial scale. Membrane separation using polyethersulfone type was found to have a good potential in crude palm oil degumming. However, an appropriate method has to be developed to clean the membranes.